Studi Kualitatif Pertumbuhan Populasi Kambing Paket Bantuan Kebijakan Crash Program dan Faktor – Faktor Yang Mempengaruhinya Di Kampung Sekendi Distrik Teminabuan Kabupaten Sorong Selatan - T Sraun (Universitas Andalas, 2012)
Distribution of crash program-based local goat as an object of agriculture policy of Crash Program implemented in 1995, and it has done throught the members of Sekendi community village at district of Teminabuan of South Sorong regency as targeted group. The program aim is increasing of the goat population as the goal and the cattle population as the subject. Village of Sekendi was chosed as visited sites. This research showed that the population growth of goat decreased which both the population of goat and farmer population dropped by 73.68% and 66.67%, respectively. Uncertaintly of socio-economic and feeding ration, reproduction and management are factors determining population growth of goat. The failure of crash program based-goat failed to achieve the goal.